Southern Paiute : a portrait - Hebner, Logan (Utah State University Press, 2010)
Now little recognized by their neighbors, Southern Paiutes once had homelands that included much of the vast Colorado Plateau, Great Basin, and Mojave Desert. From the Four Corners' San Juan River to California's lower Colorado, from Death Valley to Canyonlands, from Capitol Reef to the Grand Canyon, Paiutes lived in many small, widespread communities. They still do, but the communities are fewer, smaller, and mostly deprived of the lands and resources that sustained traditional lives. To portray a people and the individuals who comprise it, William Logan Hebner and Michael L. Pl.